Bacterial vaginosis and adverse outcomes among full-term infants: a cohort study. Issue 1 (December 2016) - Dingens, Adam; Fairfortune, Tessa; Reed, Susan; Mitchell, Caroline
Abstract Background Bacterial vaginosis (BV) during pregnancy is a well-established risk factor for preterm birth and other preterm pregnancy complications. Little is known about adverse neonatal outcomes associated with BV exposure in full-term births, nor its influence on adverse outcomes independent of its effect on gestational age. The purpose of this study was to examine the relationship between BV during pregnancy and adverse neonatal outcomes among full-term and preterm infants. Methods We conducted a retrospective cohort study of Washington State mother/infant pairs from 2003-2013, stratified by full-term (primary outcomes) and preterm births (secondary outcomes). BV-exposed and unexposed women were frequency-matched based on year of delivery. BV exposure and adverse outcomes [assisted ventilation/respiratory distress, neonatal intensive care unit (NICU) admission, neonatal sepsis, fetal mortality, and infant mortality] were identified using birth certificates, ICD-9 codes from linked hospital records, and death certificates. Associations between BV exposure and outcomes were assessed using multivariable Poisson regression, adjusted for maternal demographics, gestational age, and other pregnancy complications, including infections. Results A total of 12, 340 mother/infant pairs were included: 2, 468 BV-exposed (2198 term, 267 preterm) and 9, 872 BV unexposed (9156 term, 708 preterm). Among full-term infants, BV-exposed mothers were younger, more likely to be Black or Hispanic, more likely to have had a sexually transmitted infection, and less likely to have a college degree than unexposed mothers. Term BV exposed infants were more likely to have meconium at delivery. Following adjustment, BV was associated with an increased risk of assisted ventilation/respiratory distress at birth (aRR = 1.28, 95 % CI 1.02-1.61), NICU admission (aRR = 1.42, 95 % CI 1.11-1.82), and neonatal sepsis (aRR = 1.60, 95 % CI 1.13-2.27) among full-term infants. These associations were independent of the presence of chorioamnionitis or meconium. Among preterm infants, BV-exposure was associated with an increased risk for NICU admissions only (aRR = 1.24, 95 % CI 1.04-1.46). Conclusions BV exposure during pregnancy is associated with adverse neonatal outcomes even among infants born full-term. These findings amongst full-term infants are novel, and highlight neonatal implications of BV in pregnancy independent of BV's effect on preterm birth.